Traduzindo ideias de gestão: a influência das consultorias na profissionalização do campo da administração - Valverde, Jéssica Monteiro (2021)
Consultancies are knowledge-based organizations that have gained market share in recent years. The growth of consultancies is anchored in their ability to circulate management ideas among organizations of different sizes and segments, contributing to the development of the Management industry and the phenomenon of managerialism in contemporary society. Using the perspective of Scandinavian Organizational Institutionalism and its notion of “translation” to explain how abstract ideas and concepts can be applied in local contexts, this research aimed to investigate how the translation and editing of management concepts carried out by organizational consulting companies contribute to the professionalization of the Management field, and it was operationalized through the following specific goals: (i) to identify which competencies are necessary for consulting professionals; (ii) explain the secondary socialization process for new consultants; (iii) analyze how the translation and editing of management concepts by consulting professionals takes place; and, (iv) to analyze which are the influential logics in the process of translation and editing of management concepts carried out by the consultants, and their effects on the professionalization of the Management field. This interpretive study is qualitative and exploratory-descriptive. The empirical material was apprehended through semi-structured interviews conducted with 16 consultants in the cities of João Pessoa, Campina Grande and Guarabira, all in the state of Paraíba, Brazil. As a method of analysis, a qualitative content analysis was initially carried out, which served as the basis for a rhetorical analysis of the consultants. Results indicate that the consultants acquire the necessary skills for their performance in processes of secondary socialization of higher education and/or professional experiences that put them in contact with vocabularies specific to Management, as well as symbols and “ways of doing” proper to the Management profession. In this way, the plurality of theoretical and practical knowledge provides consultants with the ability to translate the acquired knowledge, which uses rhetoric as a strategic tool to build meanings shared with its clients, in order to obtain and maintain their legitimacy. The study also identified that the consultants are mostly governed by the professional logic of Management and, thus, during their performance, they awaken and promulgate practices located in their “ways of doing” which, when replicated in different organizations, contribute to the professionalization of the field, hence circulating management ideas.